Graphene Oxide, a Novel Nanomaterial as Soil Water Retention Agent, Dramatically Enhances Drought Stress Tolerance in Soybean Plants - Zhao, Lin; Wang, Wei; Fu, Xiaohong; Liu, An; Cao, Jinfeng; Liu, Jianfeng (Frontiers in Plant Science, 2022)
Drought is one of the most severe environmental stressors that place major constraints on the growth of soybeans (Glycine max L.). Graphene oxide (GO) is a nanomaterial that can promote plant growth without toxic effects. In this study, the physiological and molecular responses to drought stress with GO treatment were examined. We discovered that the relative water content (RWC) of stems and leaves treated with GO was 127% and 128% higher than that of the WT plants, respectively. The root parameters in GO-treated soybeans were increased by 33.41%, 37.88%, 34.25%, and 34.72% than WT plants in total root length, root surface area, root diameter, and root volume, respectively. The activities of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX) were also increased by 29.16%, 57.03%, 27.67%, and 66.43%, respectively. However, the relative conductivity (REC), malondialdehyde (MDA), and hydrogen peroxide (H2O2) accumulation were remarkably decreased. Furthermore, the content of drought-related hormones JA, SA and ABA in GO-treated soybeans increased by 32.16%, 33.68% and 67.10% than WT plants, respectively. At the molecular level, the effects of GO treatment were manifested by relatively higher expression of four drought-related genes: GmP5CS, GmGOLS, GmDREB1, and GmNCED1. Taken together, our findings revealed that GO could directly increase plant defense enzymes, hormone content, and the expression of drought-related genes, thereby improving the soybean’s ability to resist drought. These findings could provide new opportunities for improving drought tolerance in soybeans through effective soil water retention agents.